Effects of selective EP2 receptor agonist, omidenepag, on trabecular meshwork cells, Schlemm’s canal endothelial cells and ciliary muscle contraction - Natsuko Nakamura (Nature Portfolio, 2021)
Abstract This study investigated the effects of omidenepag (OMD), a novel selective EP2 receptor agonist, on human trabecular meshwork (HTM) cells, monkey Schlemm’s canal endothelial (SCE) cells, and porcine ciliary muscle (CM) to clarify the mechanism of intraocular pressure (IOP) reduction involving conventional outflow pathway. In HTM and SCE cells, the effects of OMD on transforming growth factor-β2 (TGF-β2)-induced changes were examined. The expression of actin cytoskeleton and extracellular matrix (ECM) proteins, myosin light chain (MLC) phosphorylation in HTM cells were evaluated using real-time quantitative PCR, immunocytochemistry, and western blotting. The expression of barrier-related proteins, ZO-1 and β-catenin, and permeability of SCE cells were evaluated using immunocytochemistry and transendothelial electrical resistance. The CM contraction was determined by contractibility assay. OMD significantly inhibited expression of TGF-β2 induced mRNA, protein, and MLC-phosphorylation on cytoskeletal and ECM remodeling in the HTM dose dependently. In SCE cells, OMD suppressed TGF-β2-induced expression of the barrier-related proteins and decreased SCE monolayer permeability. OMD at 3 µM significantly inhibited CM contraction, however, the effect was not significant at lower concentrations. IOP lowering effect of OMD through conventional outflow pathway is exerted by increasing outflow facilities with the modulation of TM cell fibrosis and SCE cell permeability.